2006
DOI: 10.21273/hortsci.41.3.586
|View full text |Cite
|
Sign up to set email alerts
|

A Five-year Study on the Effect of Cluster Thinning on Yield and Fruit Composition of `Chambourcin' Grapevines

Abstract: `Chambourcin' (Vitis sp.) is a French-American hybrid cultivar that has the propensity to overcrop, and its performance under cool climate and short growing season is not known. This study was conducted for five years (2000 to 2004) to evaluate the effect of three levels of cluster thinning (10, 20, and 30 clusters per vine) on yield and fruit composition of `Chambourcin' grown in northeastern Ohio. Cluster thinning reduced yield per vine and crop load, but increased pruning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 0 publications
3
25
2
2
Order By: Relevance
“…5A; Table 1) primarily because of larger interannual variation in reproductive mass. The interannual variability in fruit mass that we observed is consistent with observations from other multiyear data sets (Dami et al, 2006). It is understood that suboptimal environmental conditions in short but critical periods may adversely affect reproductive development without substantial or lasting effect on vegetative growth in perennial fruit crops, including grapes (e.g., Esparza et al, 2001;Keller and Mills, 2007;McCarthy, 1997;Stephenson et al, 2003).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…5A; Table 1) primarily because of larger interannual variation in reproductive mass. The interannual variability in fruit mass that we observed is consistent with observations from other multiyear data sets (Dami et al, 2006). It is understood that suboptimal environmental conditions in short but critical periods may adversely affect reproductive development without substantial or lasting effect on vegetative growth in perennial fruit crops, including grapes (e.g., Esparza et al, 2001;Keller and Mills, 2007;McCarthy, 1997;Stephenson et al, 2003).…”
Section: Resultssupporting
confidence: 88%
“…The inclusion of ''noncount'' shoots in the data set contributed substantially to this outcome. Number of clusters, a significant component of yield (e.g., Dami et al, 2006;Edson et al, 1993;Wolpert and Vilas, 1992), is the sole variable measured by some grape processors in predicting yields, which is a reasonable approach given that cluster number essentially is fixed early in the season (barring catastrophic disease incidence). Values of fruit mass per shoot as a function of cluster number per shoot appeared to fall into two populations; only after fruit mass per shoot exceeded %25 g was the number of clusters per shoot associated with total fruit mass (r = 0.87; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, 'Chambourcin' requires a relatively long growing season to ripen its fruit; therefore, the vines are vulnerable to early fall frost in cool seasons and cannot acquire adequate cold acclimation, which results in winter injury. A five-year study with 'Chambourcin' demonstrated that the average fall frost date was 1 d later than harvest, resulting in inadequate acclimation and subsequent winter injury (Dami et al, 2006).…”
mentioning
confidence: 99%
“…Vine spacing can also have a large impact on grape yield and composition (Dami et al, 2005;Reynolds et al, 2004), a factor that is especially important when comparing results from our trial with results from others. Research also indicates that yield and composition of cold-climate grapes can be improved by vine management practices, such as cluster thinning or leaf pulling (Dami et al, 2006;Riesterer-Loper et al, 2019), practices that were not performed during our trial. Therefore, the potential shown by the cultivars in our trial represents results that could likely be improved upon by implementing specific training systems, vine spacing arrangements, and management practices that can optimize the yield and berry composition of each cultivar in Iowa's climate.…”
Section: Redmentioning
confidence: 94%